"Starting from scratch to looking really clean and professional": how students' productive labor legitimizes collegiate esports. Issue 2 (15th March 2022) - Harris, Brandon C.; Hansen, Jared; Can, Onder; Rahman, Md Waseq Ur; Foxman, Maxwell; Cote, Amanda C.; Fickle, Tara
ABSTRACT: This article analyzes the relationship between student productive labor, or the creation of media content like podcasts or graphic designs, and the institutionalization of collegiate esports. Through 19 semi-structured interviews with students and professionals involved in different areas around collegiate esports, we found that students' productive labor was a key force in the institutionalization of collegiate esports that generated value for university institutions, the collegiate esports program, and themselves. Student journalists, shoutcasters, and graphic designers perform immaterial labor (Lazzarato, M., 1996 Immaterial labour. Radical thought in Italy: A potential politics, 133–47) that combines technical expertise and familiarity with esports cultural norms to produce content for their university programs. Students reported their excitement to pursue careers throughout the esports industry while acknowledging the stiff competition and precarious nature of employment, resonating with Bulut's (2020, A precarious game: The illusion of dream jobs in the video game industry ) discussion of ludopolitics to examine who can play games versus who can work in the game industry. The article thus addresses the benefits, and risks, inherent in colleges' reliance on student labor to structure and promote their nascent esports programs.